ANALYSIS OF IMAGERY IN FIVE SELECTED POEMS BY MAYA ANGELOU - Siti Angreini Arbi (British (Jurnal Bahasa dan Sastra Inggris), 2018)
This research is qualitative descriptive research that analyzes five selected poems of Maya Angelou “I Know Why the Caged Bird Sing, Still I Rise, Phenomenal Woman, When I Think about My Self and the last is Alone”. The researcher used qualitative method and structural approach to know what kinds of imagery that used in five selected poems by Maya Angelou “I Know Why the Caged Bird Sing, Still I Rise, Phenomenal Woman, When I Think about My Self and the last is Alone”. Then, the data were collected from five poems selected by Maya Angelou. In the process analyzed, the researcher read the poem “I Know Why The Caged Bird Sing, Still I Rise, Phenomenal Woman, When I Think About My Self and the last is Alone” and using five steps based on the technique of analyzing the data by using structural approach to find what kinds of imagery that used in poem “I Know Why the Caged Bird Sing, Still I Rise, Phenomenal Woman, When I Think About My Self and the last is Alone” by Maya Angelou. Then based on the result of this analyzed, the researcher found there are four types of imagery that Maya Angelou used in his poem “I Know Why the Caged Bird Sing, Still I Rise, Phenomenal Woman, When I Think About My Self and the last is Alone” Those are visual imagery, auditory imagery, tactile imagery, gustatory imagery and last is kinesthetic imagery, but the kinds of imagery that very dominant used is auditory imagery. Keywords: Poetry, Imagery, Method and Approach